Ultrasonic assisted tubular channel angular pressing process - Faraji, G.; Ebrahimi, M.; Bushroa, Abdul Razak (Elsevier, 2014)
Improvement of severe plastic deformation method׳s efficiency by decreasing the pressing load is an important challenge for industrialization of these processes. A novel severe plastic deformation technique entitled tubular channel angular pressing process was recently proposed and experimented. The current study investigates the influences of ultrasonic vibration (UV) amplitudes in axial and radial directions on the deformation behavior and required punch force of TCAP process using finite element analysis. The numerical results indicated that the magnitude of imposed effective strain and the uniformity of strain distribution are enhanced by applying ultrasonic vibration. In addition, higher UV amplitude leads to an increment of effective strain and enhancement of strain dispersal. Furthermore, the simulated results showed that application of ultrasonic vibration needs lower pressing force to carry out TCAP process. Furthermore, a much lower punch load is required by adding vibration amplitude. It is found that the influence of radial directional UV is a more dominant factor than axial one on both the strain behavior and the pressing force. It is believed that ultrasonic vibration of TCAP die is more impressive than UV of either mandrel or punch.